Flood Control Measures in One Municipality in Camarines Sur, Philippines: Bases for Community-Based Flood Control Interventions - Romeo Jr. Sotto (Camarines Sur Polytechnic Colleges, 2022)
Hydrometeorological hazards like flooding are inevitable; these affect agriculture and impact the economy for a prolonged duration. This research study was conducted to determine and assess the flood control measures in the municipality of Nabua in the Province of Camarines Sur, Philippines as bases for developing community-based flood control interventions. Using the descriptive evaluative survey method with a validated questionnaire as the primary data gathering instrument, gathered data were computed, tabulated, analyzed, and interpreted. It has shown that the degree of implementation of the flood control measures is high for structural and non-structural flood management. The null hypothesis is rejected. The difference between the responses of the respondents was significant. The extent of the effect of the factors directly influences the implementation of the flood control measures. It can be concluded that the Municipality of Nabua controls flooding primarily through its flood control infrastructures that are strategically situated in the municipality, human resources, and collaboration and linkages. Moreover, the responses of the respondents are significantly different. Improvement and upgrading of its physical facilities and equipment to acquire real-time information; intensifying its campaign and information drive to build a more vital link between the municipality and its constituents, and information dissemination using social media and communications technology can increase awareness, mitigation, control, and response to flooding are thereby recommended. The community-based interventions on flood control can serve as a guide and an eye-opener for the local government unit of Nabua to promulgate and enact municipal ordinances about flood control.